Numerical modeling of the face reinforcement of Djebel El-Kantour tunnel face (highway east-west) - Messast, Salah; Hazem, Mustapha; Bousbia, Nawel; Mokhbi, Hichem (Journal of Applied Engineering Science & Technology, 2014)
The extension of communication ways (roads, highways, railways) often involves difficult crossings that usually lead to the construction of important structures such as tunnels. Similarly congestion on ground surface in cities necessitates the construction of underground structures (roads and metros). Terrain stability during construction especially in the coalface is one of the major problems related to the construction of these structures. This paper presents numerical modeling of the mechanical behavior of the rock face of the DJebel El-Kantour tunnel (East West Highway) reinforced by fits. In order to minimize on maximum the cost of numerical simulations, the reliability of three methods of homogenization of reinforced soil (improving cohesion, improving the cohesion and angle of friction and ultimately improve the Young's modulus) is tested by comparing the results of numerical simulations to the displacements measured insitu. Résumé : L’extension des voies de communication (routes, autoroutes, voies ferrées) impose souvent des franchissements difficiles qui conduisent généralement à la construction d’ouvrages importants tel que les tunnels. De même l’encombrement de la surface de sol dans les villes rend nécessaire la construction d’ouvrages souterrains (voiries et métros).  La stabilité du terrain pendant les travaux notamment au front de taille est l’un des problèmes majeurs liés à la construction de ces ouvrages. Cet article présente la modélisation numérique du comportement mécanique du front de taille du tunnel Djebel El-Kantour (Autoroute est ouest) renforcé par des fits.  Dans le but de minimiser au maximum le cout des simulations numériques, la fiabilité de trois méthodes d’homogénéisation des sols renforcés (amélioration de la cohésion, amélioration de la cohésion et l’angle de frottement et en fin amélioration du module de Young) sera testée, en comparant les résultats des simulations numériques aux mesures des déplacements insitu. Mots clés : Renforcement, sol, homogénéisation, tunnel, déplacement.
Keywords: Reinforcement, soil, homogenization, tunnel, displacement